Determination Of Optimal Longwall Face Methane Monitoring Locations - A. B. Cecala (Society for Mining, Metallurgy & Exploration, 1995)
The US Bureau of Mines performed a study to determine optimal locations for longwall face methane monitoring equipment. Longwall face ignitions continue to be a concern to the US coal mining industry. Gains in ignition control technology have been somewhat negated by advances in longwall productivity. More reliable, heavy duty longwall face systems generate higher production rates and increase methane liberation rates. These rates will likely continue to rise as further coal production increases occur. Efforts will continue in the areas of methane drainage, methane containment and methane dilution. In addition, more effective face methane monitoring is needed. As technology continues toward automated longwall panels, the importance of monitoring for methane at the shearer becomes even more significant. Since the primary face ignition source is the shearer mining machine, the Bureau ran tests to determine the best location to take methane readings on the shearer. This information, in conjunction with data obtained from field studies, provides a knowledge base for selecting optimum face methane monitoring locations.